Management of financial support for enterprise development - Novikova, I. V. (Ways to Improve Construction Efficiency, 2018)
The article substantiates the theoretical provisions and practical recommendations for the management of financial support for enterprise development, considers the main directions of forming an effective process for managing financial support for enterprise development. The content of the concept "process of financial management of enterprise development" is substantiated. The key characteristics and features of financial support of enterprise development are generalized.